Trends in prescription and cost of Sativex, a cannabinoid-based medicine, in treating patients with multiple sclerosis in England - Farideh A. Javid; Anam Alam; Emily Williams; Sidhra Sajid Malik; Usama Mohayuddin; Syed Shahzad Hasan (Taylor & Francis Group, 2024)
ABSTRACTAim: Cannabis-based medication has recently been made available in the NHS for reducing pain and spasticity in patients with multiple sclerosis (MS). The currently available preparation of Sativex (nabiximols) contains a combination of botanical cannabis extracts with cannabidiol (CBD) and tetrahydrocannabinol (THC) with almost equal amounts in addition to minor cannabinoids and terpenoids and is delivered via an oro-mucosal spray. The present study aims to examine the use and trends in prescribing cannabinoid-based Sativex to control pain in patients diagnosed with MS.Methods: Primary care prescribing data for cannabinoid-based Sativex (2013-2022) from the Prescription Cost Analysis were extracted and analysed. Linear regression analyses were performed to examine prescription trends and prescription costs (average change per year).Results: There was a general increasing trend in the number of prescriptions each year, from 4.42 items dispensed per 100,000 people in 2013 to 5.15 in 2022. Overall, prescription items for cannabinoid-based Sativex increased by 0.34% per year (95% CI:−3.98, 4.67, p = 0.860) on average between 2013 and 2022. On average, a 2.43% (95% CI: −5.78, 0.92, p = 0.133) increase per year was observed for the costs of cannabinoid-based Sativex from 2013 to 2022.Conclusion: The results suggested that cannabinoid-based Sativex should be considered an option due to its effectiveness, acceptable tolerance, and safety profile in the prescribing of Sativex.